Molecular dynamics study of polyethylene chain non-isothermal crystallisation: effects of chain length and branch structure. Issue 12 (13th August 2019) - Gao, Rui; Zhao, Li; Shao, Yunqi; Liu, Zhen; He, Xuelian; Liu, Boping
ABSTRACT: The molecular dynamics simulations in this work were aimed to provide a molecular insight into chain structure effects on non-isothermal crystallisation of polyethylene (PE) chains. The crystallisation behaviours were influenced by chain length and cooling rate in linear PE chain crystallisation: C100 and C150 were unable to fold into crystals. From C1000 to C3000, crystallisation abilities became stronger as chain length increased. From C5000 to C14000, chain length had no influence on crystallisation abilities. Final morphologies changed from rotator phase to single crystal domain, and to multi crystal domains as chain length increased. The formation of multi crystal domains with longer chain was easier than with the shorter chain in identical conditions. Branch content influenced not only the crystallisation kinetics but also final morphologies in non-isothermal crystallisation. The branches were defective in nucleation process, which was reflected in the crystal growth process. Crystallisation temperature, rate and crystallinity decreased, and the morphologies became disordered as branch content increased. Changes of final morphologies from single crystal domain to multi crystal domains were found under the influence of branch content and cooling rate. Trans-rich phenomenon was observed, and the trans-state population increment was prior to crystallinity increment. Crystallisation processes began at different crystallisation temperature when the trans-state populations reached a critical value which was independent of branch content.